2008
DOI: 10.1038/bjp.2008.118
|View full text |Cite
|
Sign up to set email alerts
|

Cellular and molecular mechanisms responsible for the action of testosterone on human skeletal muscle. A basis for illegal performance enhancement

Abstract: The popularity of testosterone among drug users is due to its powerful effects on muscle strength and mass. Important mechanisms behind the myotrophic effects of testosterone were uncovered both in athletes using steroids for several years and in short-term controlled studies. Both long-term and short-term steroid usage accentuates the degree of fibre hypertrophy in human skeletal muscle by enhancing protein synthesis. A mechanism by which testosterone facilitates the hypertrophy of muscle fibres is the activa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
128
0
7

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 164 publications
(140 citation statements)
references
References 49 publications
(74 reference statements)
5
128
0
7
Order By: Relevance
“…In humans, muscle mass provides one such signal (Griggs et al, 1989; Kadi, 2008). Muscularity provides benefits in sexual selection from both inter‐ and intra‐sexual perspectives (Bribiescas, 2001; Dijkstra & Buunk, 2002; Frederick & Haselton, 2007; Gallup, White, & Gallup, 2007; Lavrakas, 1975).…”
Section: Discussionmentioning
confidence: 99%
“…In humans, muscle mass provides one such signal (Griggs et al, 1989; Kadi, 2008). Muscularity provides benefits in sexual selection from both inter‐ and intra‐sexual perspectives (Bribiescas, 2001; Dijkstra & Buunk, 2002; Frederick & Haselton, 2007; Gallup, White, & Gallup, 2007; Lavrakas, 1975).…”
Section: Discussionmentioning
confidence: 99%
“…The primary cellular targets of androgen action in skeletal muscle remain unresolved (Kadi 2008). Different studies have suggested that androgens act on satellite cells or myoblasts to increase the number of myonuclei (Mulvaney et al 1988, Joubert et al 1994, Joubert & Tobin 1995 or act on myofibers to increase protein content (Sheffield-Moore et al 1999, Ferrando et al 2002, Chen et al 2008, Ophoff et al 2009b.…”
Section: Discussionmentioning
confidence: 99%
“…While each bird in the previous study of nandrolone received a total of 120 mg nandrolone decanoate injected over a period of 4 weeks, each chicken in this study received a total dose of only about 21 mg mesterolone over the same period of time. One of the suggested mechanisms by which AASs induce muscle hypertrophy is increasing the population of myonuclear androgen receptors upon which they can act (Sinha-Hikim et al, 2004;Kadi, 2008). The activated androgen receptors then bind to selective genes within the myonucleus to increase their rates of transcription (Kadi, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…One of the suggested mechanisms by which AASs induce muscle hypertrophy is increasing the population of myonuclear androgen receptors upon which they can act (Sinha-Hikim et al, 2004;Kadi, 2008). The activated androgen receptors then bind to selective genes within the myonucleus to increase their rates of transcription (Kadi, 2008). We speculate that the higher dose of nandrolone decanoate led to a greater transcriptional activity of myonuclei, which in turn resulted in a larger MD.…”
Section: Discussionmentioning
confidence: 99%